(3oeNJUQ aj GdWHs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd eUfa gPG GdeNJUQ deG QCjJ Cf GdYeQ bUjQ , hGdcJH cKjQI GdJWhjd , hGdJLQHI NWQ , GYJeOfG Ydi gPG GdeNJUQ , dCfg bQjH Edi GdPgf ddWGdH GdeJYde s
(3BNQgG (B:s
(3aGdMei Ob hYdGLgG Ph ejhd cKjQI MJi Efg jUYH Ydi egQI GdCWHGA, hjfHZi Cf jdLC (B((3ai(B) (3CeQgG Edi GdWHjH s
(3hgh aj YTQI ebGdGJ hJfbSe cd ebGdI Edi CHhGHs
(3ocJHJ ChGFd GdebGdGJ hGdCHhGH HGdeOGO GdCMeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B223 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs